Atrial septal defect with pulmonary arterial hypertension in pregnancy : A case series - Valerinna Yogibuana; Martini, Heny; Gultom, Yosafat Hasiholan Marthin (Heart Science Journal, 2026)
Background: Congenital heart disease (CHD) ranked among the most frequently encountered structural abnormalities in humans. Acyanotic congenital heart disease (CHD) persists as a global issue, with atrial septal defect (ASD) constituting the second most prevalent form, accounting for around 10% of all CHD cases and occurring more frequently in females than in males. Pregnancy physiologically modifies the cardiovascular system and may exacerbate the clinical condition of people with atrial septal defect and pulmonary hypertension, potentially resulting in heart failure. Case Presentations: We documented five examples of pregnant patients with ASD and pulmonary hypertension (PH).  Two patients had established medical records and attended regular follow-up, one of whom underwent ASD closure.  All patients had dilation of the right atrium and ventricle, with two individuals presenting right ventricular (RV) systolic dysfunction.  All patients exhibited normal left ventricular (LV) systolic function.  Notwithstanding the oversight of a multidisciplinary heart team and intensive care management, one of our patients succumbed following cesarean section delivery.  The patient exhibited diminished right ventricular systolic function, a bidirectional shunt lesion, a significant maximal pressure gradient, and lacked any documented cardiovascular or obstetric medical history, presenting with a poor mWHO classification.   She experienced unresolved postoperative shock and bleeding. Conclusions: Managing PH secondary to CHD among pregnant patients presents significant challenges for multidisciplinary teams. Intensive perioperative care is essential to minimize mortality and morbidity in pregnant women with PH. Careful planning of optimal medical therapy, timing and delivery method, and post-natal approach is vital to improve outcomes.